Quantitative risk analysis of IT projects - Bryndza, Joanna (Ilościowa ocena ryzyka projektu informatycznego, 2011)
Risk management is a very important and unfortunately often belittled process inIT project management. Meanwhile, risk identification and analysis, as well as other elementsof this process are necessary for effective project management. The article points out theimportant role of quantitative risk analysis, and discusses the most commonly used methods:sensitivity analysis, EMV, Monte Carlo simulations, experts’ survey, decision trees and PERT.It also discusses tools to help risk analysis
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 205, s. 32-42
Keywords: project risk management methodologies; risk analysis; IT projects; quantitative risk analysis